DEVELOPING ASKING AND GIVING INFORMATION MATERIALS DEALING WITH 2013 CURRICULUM OF EIGHT GRADE OF SMP STUDENTS - Nur Ilmiah; Nur Aliyah Nur (ETERNAL (English, Teaching, Learning and Research Journal), 2018)
This research aimed to develop an English material focusing on asking and giving information material based on 2013 curriculum of the Eight Grade Student at SMPN 2 Sungguminasa, Gowa. Based on the preliminary study on Mei 2016, the writer found that both the teacher and the students did not have appropriate and understandable materials. In addition, teacher on implementing the 2013 curriculum was unpreparedness and the students faced difficulties in learning English since they didn’t have many sources except the students’ book that provided by the government. This study utilized Research and development (R&D), ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation). This research started with the analysis the result of questionnaire which had been distributed to the students, then design English material based on syllabus and students need of the materials, it continued with the development of the materials, the product is going to be implemented in the real learning and teaching and the last is evaluation, one expert is involved to check the quality of the product. In this research, teacher and expert were involved in order to validate the product. There are two aspects that they validated of the product: Organization of the Materials and Content of English material. Overall, this research presented the product which content of lesson relevant with students need and curriculum. In addition, the product was expected to be able to help both the teachers and students in learning English especially about asking and giving information material.